1981
DOI: 10.1088/0031-8949/24/4/006
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transfer and Ionization in Collisions with Hydrogen Atoms

Abstract: A review is given of the results of experimental studies of electron cap ture, loss and ionization in collisions of atomic species with hydrogen atoms. The results are considered in relation to current theoretical descriptions of the collision processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1983
1983
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 123 publications
0
3
0
Order By: Relevance
“…The summation is performed over all ion species in the plasma. The impurity contribution to the mean free path is taken into account by using the approximate relationship <a c ^v> s Z a <a §jV> [19], so that the summation is simply replaced by n e <a^v>.…”
Section: Simulation Of Results In the Stationary Casementioning
confidence: 99%
See 1 more Smart Citation
“…The summation is performed over all ion species in the plasma. The impurity contribution to the mean free path is taken into account by using the approximate relationship <a c ^v> s Z a <a §jV> [19], so that the summation is simply replaced by n e <a^v>.…”
Section: Simulation Of Results In the Stationary Casementioning
confidence: 99%
“…The last condition cannot be fulfilled for very low frequencies, as can be seen from Eqs (19) and (20), taking into account relations (21). To find out whether this condition is fulfilled for higher frequencies, f 2 must be evaluated.…”
Section: The Fokker-planck Equationmentioning
confidence: 99%
“…This ratio approaches 0.7 in the low collisional energy limit and increases to 4 for the high energies. The slow collisions of heavy low charged ions including W q+ ions (6 q 15) with the H and H 2 targets (our case) were investigated in [19][20][21]. No clear relationship between the measured σ H 2 and σ H CE cross sections was found for the studied ions, but it was shown that the behaviour of the ratio σ H 2 /σ H differs from this ratio for the highly charged projectiles.…”
Section: Charge Exchange In Low-energy Collisions: Experiments and Th...mentioning
confidence: 94%